2013
DOI: 10.1111/jcpe.12142
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stress on periodontal treatment: a longitudinal investigation using clinical and biological markers

Abstract: Patients under psychosocial stress had a poorer outcome following NPT. The assessment of psychosocial stress may be valuable in the holistic management of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 42 publications
2
49
1
1
Order By: Relevance
“…All of the studies used exclusion criteria and achieved restriction. Nine studies performed stratification of the study sample as follows: Refulio et al [28] (gender and smoking habits); Bakri et al [4] and Forte et al [32](stress exposure); three studies [33,39,41] (age and race; Spalj et al [35] (age and stress exposure); Ishisaka et al [36] (smoking habits and race); and Ng et al [37] (geographic location, high and low emotional copers). Five studies performed matching between the study groups as follows: Mousavijazi et al [38] and Bakri et al [4] matched for gender and smoking habits; Lopez et al [39] matched for age, smoking habits and initial disease extent; Chiou et al [33] performed matching for marital status and smoking habits; and Ishisaka et al [36] matched for oral hygiene and preventive measures.…”
Section: Control Of Confounding Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the studies used exclusion criteria and achieved restriction. Nine studies performed stratification of the study sample as follows: Refulio et al [28] (gender and smoking habits); Bakri et al [4] and Forte et al [32](stress exposure); three studies [33,39,41] (age and race; Spalj et al [35] (age and stress exposure); Ishisaka et al [36] (smoking habits and race); and Ng et al [37] (geographic location, high and low emotional copers). Five studies performed matching between the study groups as follows: Mousavijazi et al [38] and Bakri et al [4] matched for gender and smoking habits; Lopez et al [39] matched for age, smoking habits and initial disease extent; Chiou et al [33] performed matching for marital status and smoking habits; and Ishisaka et al [36] matched for oral hygiene and preventive measures.…”
Section: Control Of Confounding Variablesmentioning
confidence: 99%
“…Graetz et al, [42] in a 24-month prospective clinical trial, recorded the data on annual PPD and complete X-ray documentation at the baseline, at the end of the active periodontal treatment and at the last documented visit of the supportive periodontal therapy. Bakri et al, [4] recorded the clinical parameters at the baseline and 6 months after non-surgical periodontal treatment. Only 6 studies reported intraand/or inter-examiner calibration.…”
Section: Criteria Used To Define Periodontal Diseasementioning
confidence: 99%
See 3 more Smart Citations